2015
DOI: 10.1080/15226514.2015.1045125
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of Atmospheric Hydrocarbons via Bacteria Naturally Associated with Leaves of Higher Plants

Abstract: Bacteria associated with leaves of sixteen cultivated and wild plant species from all over Kuwait were analyzed by a culture-independent approach. This technique depended on partial sequencing of 16S rDNA regions in total genomic DNA from the bacterial consortia and comparing the resulting sequences with those in the GenBank database. To release bacterial cells from leaves, tough methods such as sonication co-released too much leaf chloroplasts whose DNA interfered with the bacterial DNA. A more satisfactory b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The genera Bacillus , Stenotrophomonas , Microbacterium , Pseudoxanthomonas , Ochrobactrum , and Flavobacterium were also identified, with each of them occurring as either a single isolate or two isolates and clustering into a single OTU. Each of these genera of isolates have previously been associated with PAH degradation in different environmental matrices [ 14 , 35 , 36 ]. This study reported culturable PAH-degrading bacteria isolates.…”
Section: Resultsmentioning
confidence: 99%
“…The genera Bacillus , Stenotrophomonas , Microbacterium , Pseudoxanthomonas , Ochrobactrum , and Flavobacterium were also identified, with each of them occurring as either a single isolate or two isolates and clustering into a single OTU. Each of these genera of isolates have previously been associated with PAH degradation in different environmental matrices [ 14 , 35 , 36 ]. This study reported culturable PAH-degrading bacteria isolates.…”
Section: Resultsmentioning
confidence: 99%
“…This compound has previously been detected in 34 bacterial genera (mVOC 2.0; Lemfack et al, 2018) and has been shown to have a strong antifungal activity (Fernando et al, 2005), while also playing a role in inter-organism signaling (Thibout et al, 1995). Marinobacter has previously been reported to consume volatile hydrocarbons (Ali et al, 2015), yet to the best of our knowledge no studies have reported BVOC production by this genus. Given the close association of this bacterial genus with phytoplankton, its production of the diverse range of BVOCs reported here may contribute to the complex inter-organism signaling underpinning these relationships.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, Suda et al (2008) attempted the direct extraction of phyllosphere microbial DNA using chemical reagents, without the dislodging step. In this study, we used sonication separation to dislodge microorganisms from leaves because the brush rubbing method is complex and not highly reproducible; furthermore, another study ( Ali et al, 2015 ) indicated that the DNA produced using the latter method contains substantial chloroplast contamination.…”
Section: Discussionmentioning
confidence: 99%